Behaviour of PMSG wind turbines with fractional controllers to a voltage decrease in the grid - Melício, Rui (2013)
The effect on permanent magnet synchronous generator (PMSG) wind turbines due to grid voltage decrease and fifth harmonic is studied in this paper by computer simulations. A multilevel power converter topology and two control strategies, namely fractional and integer-order controllers, are considered in order to evaluate that effect. A comparison between the two control strategies is presented. Finally, conclusions are duly drawn.